Regional Governance and Sustainability: Research towards evidence- based policy making, at the Region of Crete - Papadakis, Nikos Eystathios (Advances in Social Sciences Research Journal, 2018)
It is widely accepted that sustainable regional development can only be achieved if the concept of sustainability is strongly connected with innovation and improvement of regional governance. This task is extremely important yet demanding as long as several policy levels and areas are interconnected as well as it is crucial to equally reinvigorate the basic pillars of sustainable development, namely economy, society and the environment. Thus, in order to conclude if the basic prerequisites exist and whether there are dynamics, drawbacks as well as opportunities in the regional level, it is important to conduct research concerning the above-mentioned connected policy areas, notions and concepts. This paper aims to analyze the basic outcomes of a large-scale qualitative and quantitative research that was conducted in the region of Crete in Greece, in order to categorize the problems, challenges, opportunities and drawbacks that regional governance, encounter and propose ways-directions in order to overcome them and achieve a socially, economically and environmentally viable future.